Tinjauan Yuridis Tindak Pidana Yang Dilakukan Oleh Remaja Dengan Membawa Senjata Tajam (Studi Putusan Nomor 117/Pid.Sus/2023/PN. Bau) - G.A. Permana; LOD Abdullah; WD. Novita A.M (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The purpose of this study is to examine the application of the law to juvenile offenders convicted of carrying a sharp weapon, as reflected in Decision Number 117/Pid.Sus/2023/PN.Bau, and to identify the factors considered by judges in imposing sentences on juvenile offenders who commit the offense of carrying a sharp weapon. This study employs a normative legal research method, which focuses on the analysis of statutory regulations, legal principles, and relevant court decisions. The results of the study indicate that the application of the law in Decision Number 117/Pid.Sus/2023/PN.Bau is consistent with the applicable legal provisions. However, in juvenile cases, the application of the law should continue to prioritize a humane approach and child protection in order to achieve substantive justice. Furthermore, the study finds that the judges' considerations integrate juridical, sociological, and philosophical aspects. The balance among these three aspects must be maintained to ensure that the best interests of the child and the objectives of rehabilitation remain the primary considerations in every judicial decision.